Efficacy of 2 L versus 3 L polyethylene glycol in bowel preparation: a real-world study - LI Jiaojun; LI Jiaojun; TAN Xianhao; TAN Xianhao; ZHANG Chen (陆军军医大学学报)
‍Objective‍　‍To compare the efficacy of 2 L and 3 L polyethylene glycol (PEG) electrolyte solution for bowel preparation in a real-world setting. Methods A real-world, single-center cohort study was conducted on the individuals undergoing colonoscopy in Department of Gastroenterology of Chengdu Third People’s Hospital between May and October 2023. Based on our inclusion and exclusion criteria, they were given 2 L (n=4 684) and 3 L (n=3 700) PEG electrolyte solution for bowel preparation. The primary outcome indicator was the adequacy of bowel preparation by Boston bowel preparation score (BBPS). Secondary outcome indicators included the BBPS score, polyp detection rate (PDR), tolerability, compliance, and incidence of adverse events. Results‍　‍The adequacy rate of bowel preparation was 94.35% in the 3 L group, significantly higher than that of the 2 L group (91.29%, P<0.001). The 3 L group obtained a higher BBPS score then the 2 L group (6.92±1.06 vs 6.81±1.14, P<0.001). But there was no statistical difference in the PDR between the 2 groups (P=0.073). And the rate of PEG completion (P=0.810), administration of low residue diet as required (P=0.094) or use of dimethicone (P=0.072) were comparable between the 2 groups. However, the incidences of vomiting (4.5% vs 3.2%, P=0.002), abdominal discomfort (5.0% vs 3.9%, P=0.011) and sleep disturbance (18.0% vs 14.6%, P<0.001) were obviously higher in the 3 L group than the 2 L group. Conclusion In a real-world setting, 2 L PEG is a considerably safe and effective regimen for bowel preparation.